2021
DOI: 10.1007/s10461-021-03385-8
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Preferences of Two Different Community Models of ART Delivery in a High Prevalence Urban Setting in Zambia: Cluster-Randomized Trial, Nested in the HPTN 071 (PopART) Study

Abstract: Community delivery of Antiretroviral therapy (ART) is a novel innovation to increase sustainable ART coverage for People living with HIV (PLHIV) in resource limited settings. Within a nested cluster-randomised sub-study in two urban communities that participated in the HPTN 071 (PopART) trial in Zambia we investigated individual acceptability and preferences for ART delivery models. Stable PLHIV were enrolled in a cluster-randomized trial of three different models of ART: Facility-based delivery (SoC), Home-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
3
1
Order By: Relevance
“…High retention rates in nonclinic-based groups (adherence clubs) in South Africa surpassed those of standard of care, 40 and in Zambia, retention rates were high and surpassed those of a home-based care model. 41 However, in this study, the number of patients remaining in their assigned study group was significantly lower in the intervention group. This high rate of attrition within the Co-ops group, most of which occurred before the first community meeting, had several causes.…”
Section: Discussioncontrasting
confidence: 58%
“…High retention rates in nonclinic-based groups (adherence clubs) in South Africa surpassed those of standard of care, 40 and in Zambia, retention rates were high and surpassed those of a home-based care model. 41 However, in this study, the number of patients remaining in their assigned study group was significantly lower in the intervention group. This high rate of attrition within the Co-ops group, most of which occurred before the first community meeting, had several causes.…”
Section: Discussioncontrasting
confidence: 58%
“…Drug shops and pharmacies play an important role in the provision of contraceptives, filling gaps in public sector service coverage in urban areas, particularly for vulnerable and harder-to-reach populations such as young and unmarried women (and men), as they may feel more comfortable at these sites [56]. With targeting, it is likely that contraceptive uptake can be increased-for example, in Bangladesh, a program based in slums successfully increased modern contraceptive use among married women of reproductive age (15-49 years) by 9 percentage points to reach 62%, higher than even nonslum areas (56%), reversing the intra-urban differential [26,57]. Localized social networks in slums have been linked to the spread of misinformation about contraceptive methods and services that may create stigma for those seeking care and may dissuade young adults from utilizing SRH services [58].…”
Section: Health Facilities and Service Provision In Urban Settingsmentioning
confidence: 99%
“…The Urban Environment and Disparities in Sexual and Reproductive Health Outcomes in the Global South: a Scoping Review of stigma, particularly among adolescents and FSWs [24,29,31,59]. For HIV testing and treatment programs, one study in urban Zambia found a higher preference for home-based models because they reported harsh treatment by clinic workers and long wait times at facilities [57]. Most often at private facilities, providers may impose policies and procedures to restrict FP methods and impede clients' access to FP based on age, parity, partner consent, and marital status [60][61][62][63].…”
Section: Health Facilities and Service Provision In Urban Settingsmentioning
confidence: 99%
“…21 A recent systematic review of studies from the USA concluded that nurses were 40% more likely than doctors to prescribe PrEP. 22 Experience from task sharing of ART shows that clients often prefer receiving care closer to their homes, 23 and that this preference translates into improved retention in care and long-term clinical outcomes when care is decentralised. 5 Task sharing can also improve the cost-effectiveness and efficiency of health systems.…”
Section: Nurse-led Prep Provisionmentioning
confidence: 99%